2020
DOI: 10.2196/24163
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Artificial Intelligence–Based Automated Recommendation System for Clinical Laboratory Tests: Retrospective Analysis of the National Health Insurance Database

Abstract: Background Laboratory tests are considered an essential part of patient safety as patients’ screening, diagnosis, and follow-up are solely based on laboratory tests. Diagnosis of patients could be wrong, missed, or delayed if laboratory tests are performed erroneously. However, recognizing the value of correct laboratory test ordering remains underestimated by policymakers and clinicians. Nowadays, artificial intelligence methods such as machine learning and deep learning (DL) have been extensively… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…Currently, few published articles deal with the issue of applying AI algorithms to laboratory test selection. Islam et al [ 56 , 57 ] have published two such studies, one of which in this issue, where they developed a deep learning algorithm based on retrospective patient data to predict appropriate laboratory tests. Xu et al [ 58 ] aimed to identify superfluous tests in existing lab orders by estimating normal test results within a retrospective dataset.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, few published articles deal with the issue of applying AI algorithms to laboratory test selection. Islam et al [ 56 , 57 ] have published two such studies, one of which in this issue, where they developed a deep learning algorithm based on retrospective patient data to predict appropriate laboratory tests. Xu et al [ 58 ] aimed to identify superfluous tests in existing lab orders by estimating normal test results within a retrospective dataset.…”
Section: Discussionmentioning
confidence: 99%
“…Deep learning (DL) models can accurately and effectively identify proper laboratory tests. AI models developed based on DL had the good discriminative abilities required for further laboratory testing and for extrapolation using routinely collected electronic health record data [31,32]. Xu et al [33] 86 -iLABMED conducted a retrospective study of 116 637 inpatients using ML models and confirmed that redundant non-essential medical tests had been performed.…”
Section: Optimized Selection Of Medical Testsmentioning
confidence: 97%
“…Deep learning (DL) models can accurately and effectively identify proper laboratory tests. AI models developed based on DL had the good discriminative abilities required for further laboratory testing and for extrapolation using routinely collected electronic health record data [31, 32]. Xu et al.…”
Section: Construction Of a Patient‐centered Medicine System Through T...mentioning
confidence: 99%
“…Using deep learning-based systems and retrospective NHIRD data for a given condition, one team developed automated laboratory test recommendation systems drawing on EHR data. This approach could reduce both over-and underutilization of tests to improve patient care and prevent unnecessary costs [38,39]. Similarly, private corporations have joined the effort.…”
Section: Advancing Healthcare Withmentioning
confidence: 99%